Pengaruh Budaya Organisasi, Kompetensi dan Penempatan terhadap Kinerja Pegawai Negeri Sipil pada Dinas Pendidikan Kota Sungai Penuh - Desi, Dona Elvia (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study aims to determine the influence and magnitude of the influence of Organizational Culture, Competence and Placement on the Performance of Civil Servants in Education Authorities Of Sungai Penuh City Simultaneously and partially. The population of this study is all civil servants in Education Authorities Of Sungai Penuh City, which numbered 44 people. Data were collected using a questionnaire that had been tested for validity and reliability. The data analysis technique used is multiple linear regression. The results showed that Organizational Culture influences the Performance of Civil Servants at the Education. Authorities Of Sungai Penuh City, this is evidenced by t arithmetic > t table (4.896 > 2.02108). Competence influences the Civil Servants in Education Authorities Of Sungai Penuh City, this is evidenced by t arithmetic > t table (2.493 > 2.02108). Placement influences the Civil Servants in Education Authorities Of Sungai Penuh City, this is evidenced by t arithmetic > t table (3.477> 2.02108). Simultaneously there is a significant influence between Organizational Culture, Competence and Placement on the Performance of Civil Servants in Education Authorities Of Sungai Penuh City, which can be proven by F arithmetic > F table (33,203 > 3.15). The influence of Organizational Culture, Competence and Placement on the Performance of Civil Servants Education Authorities Of Sungai Penuh City Is 79%. While the remaining 21% is explained by other causative factors not examined in this study.